The MUP Zagros Project: tracking the Middle–Upper Palaeolithic transition in the Kermanshah region, west-central Zagros, Iran. (20th January 2017) - Heydari-Guran, Saman; Ghasidian, Elham
Abstract : In recent decades, the Eurasian Middle–Upper Palaeolithic (M–UP) transition has been a topic of major interest among palaeoanthropologists. Great progress has been made in several domains, particularly palaeogenetics, which have revealed the complex ancestry of early Eurasians. This progress—including the identification of a ghost lineage of Eurasians in the Middle East—is providing important new biogeographical hypotheses. A key region for such topics is the Iranian Plateau—an area that has so far not been subject to intensive research.